'The uses of boredom': affect, attention, and absorption in the fiction of Don DeLillo. Issue 1 (2nd January 2019) - Manning, Nicholas
ABSTRACT: In an increasingly stimulated and stimulating modernity, is it only the bored mind which is truly free? Does boredom constitute a fundamental dissolution of the distracted modern subject, in an unproductive disengagement from both world and self, or may it rather represent a paradoxically active rebellion against those sociopolitical forces which demand ever more intense modes of attention as a means of control? Rather than the efficacious protagonists of Romantic idealism or the homo faber of post-industrial enterprise, Don DeLillo's fiction frequently presents us with characters transformed into ambiguous spectators both of history and their own lives. Even bored spectators, however, are not necessarily passive beings: though their attention may waver into apparent apathy, though their bodies and minds may show signs of having disengaged, such disengagement, beyond a simply dispassionate lethargy, may be viewed as a meaningful backlash as much against the objects of their contemplation as its technologies of delivery and display. This paper explores paradigms of affect, attention, and absorption as a means of dealing with an unassimilable intensity, with special concentration on Don DeLillo's Players, White Noise, and Falling Man .